CRIMINOLOGICAL ANALYSIS OF THE LEVEL AND DYNAMICS OF TERRORIST ATTACKS IN UKRAINE (Law and Safety, 2018)
A description and explanation of the indicators of the level and dynamics of the spread of terrorist acts in Ukraine during 2010–2016 have been provided. The author has stated the high level of terrorist attacks during the last four years and the presence of unfavorable tendencies in their reproduction. The problems of statistical accounting of terrorist acts related to the shortcomings of the legal principles of anti-terrorist activity, departmental manipulations with statistical information and other factors have been analyzed.It has been concluded that, despite the fluctuation of the level of terrorist attacks during 2014–2016, the dynamics of solving these crimes demonstrates a steady, controversial tendency to decrease in 2016 comparing to 2015 (in crime indicators). Besides, even a visual, cursory analysis of the ratio of the number of terrorist attacks and detected persons suspected of their commission in Ukraine, makes it possible to affirm either about critical ineffectiveness of the activities of the Security Service of Ukraine in detecting and investigating these crimes and the failed counter-terrorism policy of the state in the whole or about exceptional artificiality and excessive overstatement of terrorist attacks’ indicators. At the same time, the most striking difference is between recorded terrorist acts and the number of convicted persons. In this connection, the author has substantiated the necessity of radical reforming of the legal principles of the state’s response to the crimes of aggression and war crimes and the separation of the latter from the anti-terrorist measures. Otherwise, the author considers it highly problematic to provide scientific provision for anti-terrorist measures through a biased statistical situation and inadequate information models of terrorism in Ukraine.
Keywords: terrorist act, level, dynamics, statistical reporting, information model, analysis.